2019
DOI: 10.3390/cryst9120644
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Single Crystal X-Ray Analysis, Prediction and Study of Pharmacological Activity of 4-(1H-Benzo[d]imidazol-2-yl)-1-Phenyl-1H-1,2,3-triazol-5-Amine and Its Solvates

Abstract: A method for the synthesis of 4- (1H-benzo[d]imidazole-2-yl)-1-phenyl-1H-1,2,3-triazole-5-amine was developed, and the electronic and spatial structure of this molecule was studied theoretically and experimentally. The study of interaction energies between molecules by quantum-chemical calculations allows us to recognize different levels of crystal structure organization and describe the interaction types causing their formation. The classic N-H…N and C-H…N hydrogen bonds play the main role in all the studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…75–78 The synthesis of a hybrid molecule containing two pharmacophore moieties has recently been shown to be quite simple, and the obtained compound is promising from the viewpoint of its biological activity. 44 The study of the closest analogues of 4-(1 H -benzo[ d ]imidazole-2-yl)-1-phenyl-1 H -1,2,3-triazol-5-amine with various substituents corresponds to the principles of combinatorial chemistry and is aimed at finding the most promising compound for use in pharmacy. For each leader of such a search, complete polymorphic screening seems to be effective at the research stage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…75–78 The synthesis of a hybrid molecule containing two pharmacophore moieties has recently been shown to be quite simple, and the obtained compound is promising from the viewpoint of its biological activity. 44 The study of the closest analogues of 4-(1 H -benzo[ d ]imidazole-2-yl)-1-phenyl-1 H -1,2,3-triazol-5-amine with various substituents corresponds to the principles of combinatorial chemistry and is aimed at finding the most promising compound for use in pharmacy. For each leader of such a search, complete polymorphic screening seems to be effective at the research stage.…”
Section: Resultsmentioning
confidence: 99%
“…37–40 It was previously shown that hybrid molecules with the benzimidazole and 1,2,3-triazole moieties exhibit a wide range of biological activities and are promising for use in the pharmaceutical industry. 41–44…”
Section: Introductionmentioning
confidence: 99%
“…A great number of camphoric acid as well as benzimidazole derivatives exhibit different types of biological activities (Merzlikin et al, 2008;Ivachtchenko et al, 2002Ivachtchenko et al, , 2019Kovalenko et al, 1998).…”
Section: Chemical Contextmentioning
confidence: 99%